«Peonía» o la búsqueda de una lengua nacional (Castilla. Estudios de Literatura, 2024)
Peonía (1890), by Manuel Vicente Romerogarcía (1864-1917), has been read by Venezuelan critics as the novel that inaugurated Creoleism in that country. Beyond this scoop value, the work has been judged with very different criteria, ranging from staunch rejection for considering it as a work of little merit, to being a fundamental piece of national literature. Here we try to show this supposed sloppy style and heterogeneous discourses, which cover melodrama, sociology and journalism, among others, as a conscious strategy that the author uses in his need to represent Venezuelan “reality.”
Keywords: Peonía; creolism; representation; XIX century; Venezuela